Diatoms diversity and dynamics in a southern Mediterranean lagoon (Mellah, Algeria) - Draredja, M. A; Barour, C; Frihi, H; Boualleg, C; Laabir, M. (My University, 2019)
The composition and distribution of diatoms were studied using a biweekly sampling performed in three representative stations in the Mellah Lagoon (South Western Mediterranean, Algeria), during 2016. In total, 160 diatoms species - belonging to centric species (52 species) and pennate species (108 species) - were inventoried. The relative abundance of the pennate forms (67.50%) is clearly higher compared to the centric forms (32.50%). The blooms of diatoms are represented by 3 species: Chaetoceros constrictus Gran, 1897 with up to 15000 cells.L-1 (end of May), Chaetoceros sp. with up to 178320 cells.L-1 (early October), and Nitzschia longissima (Brébisson) Ralfs, 1861 with up to 200640 cells.L-1 (early September). Proliferations of three potentially toxic species: Pseudo-nitzschia group delicatissima (Cleve) Heiden, 1928 (2500 cells.L-1), Pseudo-nitzschia group seriata (Cleve) H. Peragallo, 1899 (700 cells.L-1) and Thalassionema nitzschoides (Grunow) Mereschkowsky, 1902 (210 cells.L-1), requires regular monitoring of this ecosystem where the exploitation of the shells is practiced. The diatom populations seem to be structured showing diversity (H’) and equitability (J’) indices reaching 4.56 bits.cell and 0.98 respectively, with the exception of springsummer and summer-autumn transition periods